2015
DOI: 10.1501/vetfak_0000002653
|View full text |Cite
|
Sign up to set email alerts
|

Nematode and cestode eggs scattered with cats-dogs feces and significance of public health in Samsun, Turkey

Abstract: Summary:The objectives of this study were to determine the prevalence of nematode and cestode egg contamination in cats' and dogs' fecal samples collected from public grounds (public parks, streets, walks, shelter) in Samsun, Turkey and to evaluate the potential public health risks from parasites of concern. A total of 448 stool samples, 187 cat feces and 261 dog feces, were picked up off the ground.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This can be explained by the fact that the aforementioned study was conducted exclusively on stray dogs, and parasites were screened by necropsy, probably allowing a better sensitivity comparing to the microscopic fecal examination alone (Lahmar et al, 2017). Prevalence rates reported in other regions from the Mediterranean Basin were widely different and ranged from 22% in France to 71.3% in Spain (Franc et al, 1997;Awadallah and Salem, 2015;Gurler et al, 2015;Kostopoulou et al, 2017;Matallah et al, 2018;Scaramozzino et al, 2018;Sanchez-Thevenet et al, 2019). This variation can be attributed to several factors including the study area, the diagnostic techniques used for the detection of parasites, the studied populations and their living 6.5 a 11.2 a 9.5 a 1.1 a Dipylidium caninum (%) 0 a 1 a 0 a 1.1 a Trichuris vulpis (%) 0 a 0 a 1.5 a 0 a Taenia spp.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that the aforementioned study was conducted exclusively on stray dogs, and parasites were screened by necropsy, probably allowing a better sensitivity comparing to the microscopic fecal examination alone (Lahmar et al, 2017). Prevalence rates reported in other regions from the Mediterranean Basin were widely different and ranged from 22% in France to 71.3% in Spain (Franc et al, 1997;Awadallah and Salem, 2015;Gurler et al, 2015;Kostopoulou et al, 2017;Matallah et al, 2018;Scaramozzino et al, 2018;Sanchez-Thevenet et al, 2019). This variation can be attributed to several factors including the study area, the diagnostic techniques used for the detection of parasites, the studied populations and their living 6.5 a 11.2 a 9.5 a 1.1 a Dipylidium caninum (%) 0 a 1 a 0 a 1.1 a Trichuris vulpis (%) 0 a 0 a 1.5 a 0 a Taenia spp.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, a study was carried out in Samsun which involved the analysis of 187 samples of cat faeces gathered from the streets using the flotation method. The results showed that 32.1% of these samples were found to be infected (Gürler et al, 2015). A study conducted in Kırıkkale on 100 cats' fecal examination results revealed that 48.9% of the cats had Toxocara spp.…”
Section: A B D C Discussionmentioning
confidence: 95%